Urinary Tract Infection in Children: An Update (Bangladesh Journal of Child Health, 2012)
Background: A large number of children with Urinary Tract Infection (UTI) are seen in the community by general practitioners , but there is frequently delay in treatment and not all are referred for further investigations. There is evidence that many cases are misdiagnosed. It is important to optimize diagnostic and management strategies. Result: UTI is an important cause of acute illness, it may be a marker of underlying urinary tract abnormality. Bacteria causes the large majority of UTI in children- Escherichia coli is the most common (90%) bacterial cause. Urine culture & sensitivity is the gold standard for the diagnosis and mandatory for confirmation of UTI. On culture, a colony count of more than 105/ml organisms of a single species is considered confirmatory of UTI. But there is a strong recommendation that , presence of both pyuria and at least 50,000 Colony Forming Unit (CFU) / ml of a single uropathogen in an appropriately collected specimen makes the diagnosis . There is a recommended imaging schedule in childhood UTI to detect anatomical abnormality. Management depends on type of infection. There is no role of prophylactic antibiotics to prevent febrile recurrent UTI without VUR. Conclusion: UTI is a very common disease and may be associated with renal abnormalities and long term squeale. There is debate about best investigation and management strategies. The greatest potential for prevention of renal damage lies in increased awareness, better diagnosis and management of young children with UTI in primary healthcare. DOI: http://dx.doi.org/10.3329/bjch.v36i2.13085 Bangladesh J Child Health 2012; Vol 36 (2): 90-97